Sapindus Mukorossi Fruits Gum as Sustained Release Carrier: Optimization of Gastroretentive Drug Delivery System using Simplex Lattice Design - Singhal, Mr. Peeush (Asian Journal of Pharmaceutics (AJP), 2018)
Background: Main focus of this research is to demonstrate the potential use of Sapindus mukorossi fruits gum in the development of drug delivery systems. Therefore, in this effort, gastroretentive tables of famotidine were prepared using simplex lattice design considering the concentration of okra gum, locust bean gum, and S. mukorossi fruits gum as independent variables. A response surface plot and multiple regression equations were used to estimate the result of independent variables on hardness, flag time, floating time, and drug release for 1 h, 2 h, and 8 h and for 24 h. A checkpoint batch was also ready by considering the constraints and desirability of optimized formulation to upgrade its in vitro performance. The significance of result was analyzed using analysis of variance and P < 0.05 was considered statistically significant. Results: Formulation mainly contains S. mukorossi. Fruits gum found to be satisfactory for hardness and floatability, but the combined effect of three variables was responsible for the sustained release of drug. The in vitro drug release data of checkpoint batch (F8) was found to be sustained well compared to the maximum suitable formulation (F6) of 7 runs. The â€œnâ€ value was found to be between 0.5 and 1 telling that release of drug follows anomalous (non-Fickian) diffusion mechanism indicating both diffusion and erosion mechanism from these natural gums. Predicted consequences were nearly similar to the observed investigational values representing the correctness of the design. Conclusions: Research showed S. mukorossi fruits gum (eco-friendly natural gums) can be considered as capable SR polymers.